Political Theology After the End of Metaphysics: A Revision via Jean-Luc Marion’s Critique of Onto-Theology - Almudena Molina (Religions, 2025)
This article explores the possibility of conceiving political theology beyond its traditional metaphysical foundations. Starting from Carl Schmitt’s formulation of political theology as a domain rooted in analogical and representational transfers between the theological and the political, and drawing on Jean-Luc Marion’s critique of metaphysical theology, or onto-theology, this paper interrogates the foundational assumptions of Schmitt’s political theology and assesses the viability of a non-metaphysical theo-political discourse. The article has three main aims: to elucidate the representational logic at the core of Schmitt’s political theology; to examine postmetaphysical theo-political discourses in light of Marion’s deconstruction of onto-theology; and to vindicate the legitimacy and coherence of postmodern theological-political approaches. Taking inspiration from Pseudo-Dionysius the Areopagite’s threefold theological method—affirmation, negation, and eminence—the article argues that contemporary political theology can be reframed accordingly: (1) the path of affirmation aligns with Vatter’s reading of Schmitt; (2) the path of negation resonates with Jacques Derrida’s deconstructive strategy; and (3) the path of eminence finds its expression in Marion’s phenomenology of givenness. Ultimately, this paper contends that Marion’s phenomenological approach opens a productive avenue for reconceiving theo-political discourse; it is argued that the phenomenology of givenness proposed by Marion to surpass the conceptual idols of metaphysics has significant implications for the theo-political field that remain unexplored.